The Role of Green Innovation. Cost Efficiency, and Government Incentives on the Financial Sustainability of Eco-Conscious MSMEs - Meilandri, Detti; Saputri, Novitasari Agus; Ridwan, Mohammad; Hardiwinoto, Hardiwinoto; Kristanto, Eri; Sudarmanto, Eko (International Journal of Business, Law, and Education, 2025)
This study investigates the influence of green innovation, cost efficiency, and government incentives on the financial sustainability of eco-conscious Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Using a quantitative approach and survey data collected from 200 MSMEs engaged in sustainable practices, the study employs multiple linear regression analysis with SPSS to test three proposed hypotheses. The results reveal that all three independent variables have a positive and significant impact on financial sustainability. Green innovation enables firms to differentiate their products, improve resource use, and access green markets. Cost efficiency enhances financial performance through waste reduction and operational optimization. Meanwhile, government incentives play a vital role in supporting sustainable initiatives by reducing financial and technical barriers. These findings underscore the strategic importance of integrating internal capabilities and external support to achieve long-term sustainability and competitiveness for MSMEs. The study contributes to the theoretical development of sustainable entrepreneurship and provides practical recommendations for managers and policymakers in emerging economies.